Apple orchard race - Klein, Abby.; McKinley, John (New York : Scholastic, 2010)
Freddy's first grade class is visiting an apple orchard where they will pick apples and search for a special hidden apple. Will sneaky Max cheat his way to the $5 prize?
Keywords: Apples; School field trips; Schools; Orchards; First grade (Education)